The last present - Mass, Wendy (New York : Scholastic Press, 2013)
Children's birthdays are always strange in Willow Falls, but when Connor's little sister Grace falls into a frozen state on her tenth birthday, Amanda and Leo must travel back in time to find out what force prevented Angelina from casting the blessing that would have protected her.
Keywords: Birthdays -- Juvenile fiction; Fantasy fiction